2020
DOI: 10.1519/jsc.0000000000003727
|View full text |Cite
|
Sign up to set email alerts
|

Is the Rear Foot Elevated Split Squat Unilateral? An Investigation Into the Kinetic and Kinematic Demands

Abstract: Is the rear foot elevated split squat unilateral? An investigation into the kinetic and kinematic demands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…There is evidence that unilateral and bilateral strength traning had a similar impact on muscle mass [ 46 ], girth [ 29 ] and cross-sectional area [ 47 ]. However, Helme et al, [ 48 ] found that almost 15% of the load was placed on the rear leg during the Bulgarian split squat. It could be inferred that the rear leg might be contributed to the concentric phase, which means that the lead leg might decrease force development.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that unilateral and bilateral strength traning had a similar impact on muscle mass [ 46 ], girth [ 29 ] and cross-sectional area [ 47 ]. However, Helme et al, [ 48 ] found that almost 15% of the load was placed on the rear leg during the Bulgarian split squat. It could be inferred that the rear leg might be contributed to the concentric phase, which means that the lead leg might decrease force development.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in addition to isokinetic screening, other field-based strength testing protocols are widely implemented in daily practice for assessing unilateral muscular strength, and associated inter-limb asymmetries, to aid in guiding training, rehabilitation and injury prevention. For instance, the rear-foot-elevated-split-squat-test (RFESS) can be regarded as a practical method for measuring unilateral strength in sport [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%